Penerapan Inovasi Teknologi dan Digital Marketing pada Industri Tahu dan Tempe Khas Bandungan Kab. Semarang - Prananta, Widya; Bintari, Siti Harnina; Wicaksono, Dimas; Rachmadi, Moch Faizal (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Tofu and tempeh are popular and affordable sources of plant-based protein. They also play a vital role in meeting the food needs of the Indonesian people. Besides containing plant-based protein, tofu and tempeh are also rich in fiber, calcium, iron, and sodium. Furthermore, these soybean products contain prebiotics that can help improve digestive health, isoflavones to lower cholesterol levels, and saponins to protect heart health. The various nutritional contents of soybean products, such as tofu and tempeh, must be optimized. One of the tofu and tempeh producers in Central Java is the "Asri Serasi" Tofu and Tempeh Industry in Karanglo, 06/01, Kenteng Village, Bandungan District, Central Java Province. Asri Serasi's tofu and tempeh products are only marketed at tourist markets and a few culinary stalls in the Bandungan area. However, marketing is not the only issue. In terms of production, the equipment used is still manual, such as when squeezing soybean juice and pressing tofu. Soybean juice is still extracted manually by hand, even though the company produces over 100 kg of soybean pulp per day. Some of the technologies and innovations handed over included a soybean extractor and a tofu press. Training on diversifying tofu and tempeh products into various processed foods was also conducted using a fortification method based on the use of local ingredients, including moringa leaves, cherries, and vegetables such as spinach and carrots. Digital-based business expansion assistance was also provided to address marketing challenges faced by target partners, with the active participation of students